2012
DOI: 10.11609/jott.o2863.2343-52
|View full text |Cite
|
Sign up to set email alerts
|

Population variations in the Fungoid Frog Hylarana malabarica (Anura: Ranidae) from northern Western Ghats of India

Abstract: Abstract:Widely distributed species often show interpopulation variation. Studying such variations can be helpful in understanding contributing factors and distinguishing widespread species and species complexes. We studied six populations of Hylarana malabarica distributed along the northern Western Ghats of India using morphometric and genetic analysis. Of 24 size-adjusted morphometric characters, 14 were significantly different among populations. Hierarchical clustering and discriminant analysis of morphome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This species was described by Tschudi (1838) from 'Malabar', India and subsequently reported from throughout the Western Ghats, central India (Dutta, 1997;Chanda, 2002;Daniels, 2005) and Meghalaya in Northeast India (Chanda, 2002). Padhye et al (2012) discussed genetic variability in six populations of Hylarana malabarica from Maharashtra in the Western Ghats and regarded them as a complex of species due to considerable morphological and genetic differences.…”
Section: Description Of Bnhs 5880 (Figsmentioning
confidence: 99%
“…This species was described by Tschudi (1838) from 'Malabar', India and subsequently reported from throughout the Western Ghats, central India (Dutta, 1997;Chanda, 2002;Daniels, 2005) and Meghalaya in Northeast India (Chanda, 2002). Padhye et al (2012) discussed genetic variability in six populations of Hylarana malabarica from Maharashtra in the Western Ghats and regarded them as a complex of species due to considerable morphological and genetic differences.…”
Section: Description Of Bnhs 5880 (Figsmentioning
confidence: 99%
“…All the six populations of H. malabaricus studied by Padhye et al (2012) should now be attributed to the new species H. bahuvistara based on the genetic analysis presented in the current study. Padhye et al (2012) showed that within the six populations of H. bahuvistara there are morphological as well as genetic variations in Randomly Amplified Polymorphic DNA markers. In the current study, however, we show that there is little genetic distance in the 16S rRNA gene among the populations of H. bahuvistara.…”
Section: Discussionmentioning
confidence: 65%
“…In the current study, however, we show that there is little genetic distance in the 16S rRNA gene among the populations of H. bahuvistara. Nevertheless, it is also true that the populations of H. bahuvistara are highly fragmented because of habitat fragmentation and therefore, the population variation reported by Padhye et al (2012) could be due to recent fragmentation of populations of H. bahuvistara.…”
Section: Discussionmentioning
confidence: 99%
“…Snell & Evans (2006) used RAPD to differentiate the larva of Rana arvialis and Rana temporaria that were morphologically similar. Padhye et al (2012) reported variations on the population of Hylarana malabarica in northern West Ghat, India based on RAPD markers. Therefore, this study aimed to look at the genetic polymorphism and determine the locus diversity of R. margaritifer population in Baturraden using the PCR-RAPD technique.…”
Section: Introductionmentioning
confidence: 99%